The Effect of Woman Leadership in Improving Academic Performance: Implications of Quality Assurance and Green Human Resource Management in Private Universities - Wahyuni, Sri; Zainal, Veithzal Rivai; Herminingsih, Anik; Wibowo, Mas Wahyu; Neng Ayu Sri wahyuni (Moneter: Jurnal Keuangan dan Perbankan, 2024)
Women's leadership in private universities has great potential in improving academic performance through quality assurance and environmentally friendly human resource management (GHRM). However, how women's policies influence the implementation of these two strategies is still not fully understood. This research aims to explore the role of women's leadership in improving academic performance through quality assurance and GHRM at private universities. The method used is a qualitative literature study with content analysis from various academic sources. The research results show that women's leadership significantly contributes to the effectiveness of quality assurance and GHRM implementation, which in turn improves academic performance. In conclusion, strengthening women's leadership roles and integrating mutual assurance and GHRM are important strategies for private universities to improve academic performance. The practical implications of this research include recommendations for private universities to strengthen the leadership role of women and adopt quality assurance and GHRM strategies to achieve better academic performance.